Nemački uzajamni katalog serijskih publikacija - Brzulović-Stanisavljević, Tatjana (Organizacija znanja, 2008)
The paper focuses on the German shared catalogue for serials - ZDB. The ZDB catalogue (Zeitschriftendatenbank) includes titles and holdings of serials, enables the automation of serials cataloguing and facilitats interlibrary loan. It was founded in 1973 when it was sustained by only a small number of libraries. To this day, the Bibliographic department of the National library in Berlin has been supervising and supporting it and over 4300 institutions have been included in the project. In 2000, ZDB-OPAC was created. It is updated regularly. The catalogue is published twice a year on a CD-ROM and includes titles of serials, their holdings, corporations and library addresses. The ZDB project was initially based on basic catalogue descriptionsand holdings from the ZDB catalogue and regular archiving of holdings from other networks. The updates take place once a week when the holdings are placed on the host. Since the process has been modified, some members of the ZDB network can enter their holdings even if the ZDB catalogue does not contain the publication. In German librarianship, the ZDB catalogue is the basis for all serials. The German National Library is in charge of printing the complete contents of the ZDB in January and August each year.
Keywords: katalogizacija; lokacijski podatki; serijske publikacije; vzajemni katalogi; ZDB-OPAC